Effect of GAI-3 on Clinical Outcome in Left Ventricular Systolic Dysfunction Chronic Heart Failure - Siriwattana, Khanchai (Journal of Health Science of Thailand, 2017)
Chronic Heart Failure (CHF) is a major health problem and cause of morbidity, mortality and re-hospitalization as reported by American Heart Association and European Society of Cardiology. However, there was no epidemiologic data of CHF in Thailand. There were robust evidence for effective pharmacotherapy of CHF which have been integrated into the guidelines, but many studies have shown a suboptimal utilization of recommended medication.The objective of this study was to evaluate effect of GAI-3 on clinical outcome and guidelines adherence in Left Ventricular Systolic Dysfunction CHF patients in Nakornping Hospital. This retrospective cohort study included Left Ventricular Systolic Dysfunction CHF patients admitted in Nakornping Hospital between 1 Ocotober 2009 and 30 June 2011 and were assessed after hospital discharges at least 3 months by using the medical treatment tool developed from ACC/AHA guideline 2009, ESC 2008 and Thai guideline 2008 and using adherence indicator (GAI-3) based on prescriptions of ACEIs, ARBS, β-blockers and aldosterone antagonists. Of the 93 patients included, 50.5 percent was male and mean age was 67 years. Cardiac events rate in GAI-3 categorized high/medium/low were 12.6/33.2/37.1 per 100 person-year and mean survival time from cardiac events were 666.5/573.6/533 days and CHF hospitalization rate were 17.7/33.2/33.4 per 100 person-year and mean survival time from CHF hospitalization were 666.5/573.6/554.2 days showing no statistically significant differences between the groups. The evaluation of the guideline adherence showed that the average of guideline adherence score for drugs indication was 72.7 percent, drugs type 85 percent and drug dosage 48 percent. Adherence to guideline for ACEIs was 68.5 percent, ARBs 44 percent, β-blockers 62 percent, aldosterone antagonists 62 percent and diuretics 98 percent. In conclusion, Left Ventricular Systolic Dysfunction CHF patients in Nakornping Hospital who had high GAI-3 score, showed lowest cardiac events rate and CHF hospitalization rate and longest mean survival time for cardiac events and CHF hospitalization without any statistical significance. Drug indication and drug dosage remain major problems in Nakornping Hospital based on the medical assessment tool.